Sukces w uczeniu się i jego społeczne uwarunkowania - Janicka, Monika (Neofilolog, 2010)
The present paper presents two important societal paradigms which are influential in learning cultures and understanding of school achievement. It also highlights the role school plays in socializing students. Finally, the tenets of the Polish school reform are confronted with some research concerning teachers’ routines of assessment.